Amphiphilicity of Tetraazaporphyrins Containing Four Terminal Carboxylic Acid and Four Alkyl Groups Promotes Face-On Orientation in Langmuir Films - Alinia, Zahra (Langmuir : the ACS journal of surfaces and colloids, 2024)
Control over the orientation of polycyclic aromatic dyes in thin films is paramount to tailoring their optical, electronic, and mechanical properties. Their supramolecular assembly in films is tuned here by converting the macrocyclic dyes to large amphiphiles. Two octaalkythio-substituted tetraazaporphyrins (TAPs) with one 5-carboxypentyl and one pentyl or dodecyl chain per pyrrole ring were synthesized as statistical mixtures of four regioisomers. The unsymmetrically substituted maleodinitrile precursors were prepared in good yield with a flow reactor. Neither the tetraester precursor TAPs nor the tetraacid TAPs show mesomorphism, and both belong to the small class of porphyrin derivatives that display isotropic liquid phases at or close to room temperature. Interfacial properties of the two amphiphilic tetraacids were probed using Langmuir films on aqueous subphases at different pH values, and Langmuir-Blodgett films were transferred onto mica substrates. The tetraacid with the longer dodecyl chains forms inhomogeneous films comprising a combination of monolayer, stacked macrocycles with interdigitated chains, and 3D structures, with the latter favored at higher subphase pH and higher surface pressures. In contrast, films of the tetraacid with the shorter pentyl chains yielded relatively homogeneous monolayers. The combination of atomic force microscopy imaging and packing correlations elucidated by grazing incidence X-ray diffraction suggests that these form spider-like conformations, with the macrocycles close packed and oriented parallel to the substrate (face-on). This difference in molecular packing is attributed to a possible intramolecular mixing of 5-carboxypentyl and pentyl chains that gives a better match between the footprints of the macrocycle, acid groups, and alkyl groups. The longer dodecyl chains are too large for filling the space between 5-carboxypentyl chains (mixing) and too small for filling the footprint of a TAP macrocycle. We demonstrate that by judicious tailoring of the chain length and subphase conditions, a desirable homogeneous film of face-on oriented macrocycles can be formed